Modelling of thermocouple geometry variations for improved heat transfer monitoring in smart electronic manufacturing environment. (May 2022) - Straubinger, Dániel; Illés, Balázs; Busek, David; Codreanu, Norocel; Géczy, Attila
Abstract: In this paper, the effect of different thermocouple constructions on the hot spot temperature are investigated with a modelling approach to achieve more precise soldering profile acquisition and failure analysis at different reflow soldering heat transfer methods. The paper focuses on convection-based reflow and condensation based vapour phase soldering processes and related heat transfer coefficients. Different thermocouple constructions were investigated. The parameters include the ASTM-type (K, T, J), the length of uninsulated wire length, the insulation material (PFA, PVC, PTFE, woven glass-fibre), the insulation thickness and the diameter of the hot-spot. The physical dimensions were obtained with optical microscopy for validation. Finite element analysis was performed. After validation, the results show that most parameter and geometry changes – most significantly, the uninsulated wire end – can result in non-negligible timely differences in 100 ms range between different sensors, pointing to the requirement of sorting and pairing in a symmetric measurement environment. The results can be applied in a modern manufacturing environment and in future process modelling and evaluation tasks.